Grafting a mesomorphic Schiff base onto gold nanoparticle via ester link – photoluminescence, mesomorphism, electrical conductivity and antioxidant activity. Issue 4 (16th March 2019) - Das, Nirmalendu; Borah, Debasish; Acharya, Himadri; Choudhury, Sudip; Prasad, S. Krishna; Rao, D.S. Shankar; Bhattacharjee, Chira R.
ABSTRACT: Liquid crystal-gold nanoparticle (GNP-LC) composite were accessed via covalent coupling of 4-mercaptophenol capped gold nanoparticles (GNP) and a carboxylic acid functionalised rod shaped mesomorphic Schiff base (LC). The Schiff base ligand and the composite both showed schlieren texture with distinct difference in phase transition temperature. The X-ray diffraction study suggested a smectic C mesophase for the compounds. The LC and GNP-LC, both exhibited room temperature photoluminescence when excited at 264nm.The transmission electron micrography revealed the composite to be nearly monodisphersed having almost spherical shape of ~ 2nm size. The composite material in addition to being mesomorphic exhibited pronounced AC conductivity in the semiconductor domain and antioxidant activity. Graphical Abstract: